Since our fractions have two different denominators of 2 and 4 in this equation, we can get rid of the fractions by multiplying both sides of the equation by their common denominator, which is 4.
So we have
.
Make sure you distribute the 4 through both
terms on both sides of the equation.
On the left, (4)(3/2k) is 6k and (4)(-7) is -28.
On the right, (4)(k/4) is k and (4)(-2) is -8.
So we have 6k - 28 = k - 8.
Now subtract k from both sides to get 5k - 28 = -8.
Now add 28 to both sides to get 5k = 20.
Finally, dividing both sides by 5, we find that k = 4.